Carbon nanotube-SnO2composite gas sensor prepared by electron beam evaporation - A. Wisitsoraat (2018)
Carbon nanotube (CNT) is a useful material for gas-sensing applications because of its high surface to volume ratio structure, In this work, multi-wall CNTs are incorporated into tin oxide thin film by the means of powder mixing and electron beam evaporation and the enhancement of gas-sensing properties is presented. The CNTs were combined with SnO2 powder with varying concentration in the range of 0.25-5% by weight and electron beam evaporated onto glass substrates. From AFM and TEM characterization, CNT inclusion in SnO2 thin film results in the production of circular cone protrusions of CNT clusters or single tube coated with SnO2layer. Experimental results indicate that the sensitivity to ethanol of SnO2 thin film increases by the factors of 3-6. However, if the CNT concentration is too high, the sensitivity is decreased. Moreover, the CNT doped film can operate with good sensitivity and stability at a relatively low temperature of 250-300°C. The improved gas-sensing properties should be attributed to the increasing of metal oxide surface adsorption area produced by CNT protrusion. © 2006 IEEE.